1995
DOI: 10.1021/bi00026a022
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric studies on the interaction of horse ferricytochrome c and yeast cytochrome c peroxidase

Abstract: The binding of horse ferricytochrome c to yeast cytochrome c peroxidase at pH 6.0 in 8.7 mM phosphate buffer (0.0100 M ionic strength) is characterized by a small, unfavorable enthalpy change (+1.91 +/- 0.16 kcal mol-1) and a large, positive entropy change (+37 +/- 1 eu). The free energy of binding depends strongly upon ionic strength, increasing from -9.01 to -4.51 kcal mol-1 between 0.0100 and 0.200 M ionic strength. The increase in free energy is due solely to the change in entropy over this ionic strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 59 publications
4
58
0
2
Order By: Relevance
“…As shown in Table 2, the estimated binding affinities for models B (620 μM) and C (850 μM) at 150 mM salt concentration are in agreement with experimental values, K d ≃ 100 μM and K d ≃ 300 to 1000 μM at 100 and 200 mM salt concentrations, respectively. 45,46 For the other models, the Cc/CcP complex exhibits weaker affinities between 1.5 and 2.0 mM (Fig. 2).…”
Section: Parameterization Of the Energy Functionsmentioning
confidence: 91%
“…As shown in Table 2, the estimated binding affinities for models B (620 μM) and C (850 μM) at 150 mM salt concentration are in agreement with experimental values, K d ≃ 100 μM and K d ≃ 300 to 1000 μM at 100 and 200 mM salt concentrations, respectively. 45,46 For the other models, the Cc/CcP complex exhibits weaker affinities between 1.5 and 2.0 mM (Fig. 2).…”
Section: Parameterization Of the Energy Functionsmentioning
confidence: 91%
“…Correlation of a process with osmotic pressure implies a change in the size of this population. Previous studies have shown that most protein-protein association processes in the ET reactions are usually accompanied by the release of water molecules from the interface of the complex through the hydrophobic interactions (12,(33)(34)(35)(36). The increase of osmotic pressure leads to the increase of its association constants because of the desolvation at the complex interface, as seen in the cytochrome b 5 -cytochrome c association reaction (⌬V W ϭ Ϫ47 cm 3 /mol) (34).…”
Section: Association Of Ferric P450cam With Pdx Redmentioning
confidence: 99%
“…[2][3][4][5][6] They perform less well when applied to small molecule-protein interactions, and in cases where a strong salt-dependence is observed. 7 The parameters used in calculating the enthalpy of an interaction based on surface area are derived from protein unfolding data 3,5,8 or energetics of transfer of amide and hydrocarbon compounds from dilute aqueous solution to pure liquid. 9 In both cases, charge transfer from one environment to another is under-represented in the data sets used for the parameterization.…”
Section: Introductionmentioning
confidence: 99%